Pengaruh Direct Marketing dan Kualitas Produk terhadap Minat Beli Ulang pada Live Streaming e-commerce Shopee dengan Diskon Sebagai Variabel Moderasi : Studi Kasus pada Pengguna Shopee di Kabupaten Bireuen - Putri Zianby Cintami; Ultia Rahmi; Liza Amanda; Muhammad Ferdiananda Chadafi (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
In addition to analyzing the role of discounts as a moderating variable, this study attempts to investigate how consumers' repurchase intentions in Shopee e-commerce Live streaming are impacted by direct marketing and product quality. The study used WarpPLS's path analysis as part of a quantitative methodology. Only 102 of the 112 participants who were active Shopee users with prior experience participating in live streaming sessions satisfied the requirements to be considered legitimate respondents. The results show that repurchase intention is positively and significantly impacted by direct marketing, with a p-value of 0.003 and an influence value of 0.256. Similarly, with a p-value <0.001 and an influence value of 0.401, product quality likewise significantly influences repurchase intention. Additionally, it was discovered that the discount variable strengthened the influence to 0.475 by moderating the association between direct marketing and repurchase intention. On the other hand, the influence value drops to -0.771 when discounts have a negative moderating effect on the link between product quality and repurchase intention. This suggests that offering high-quality products at unreasonably steep discounts may make customers less likely to make additional purchases. By taking into account the balance between promotional offers and product quality, this study gives e-commerce enterprises both theoretical and practical contributions to the creation of efficient promotional tactics, notably through live streaming features.